2021
DOI: 10.1093/schbul/sbab139
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dysconnectivity in Ventral Striatocortical Systems in 22q11.2 Deletion Syndrome

Abstract: 22q11.2 deletion syndrome (22q11.2DS) is a genetic neurodevelopmental disorder that represents one of the greatest known risk factors for psychosis. Previous studies in psychotic subjects without the deletion have identified a dopaminergic dysfunction in striatal regions, and dysconnectivity of striatocortical systems, as an important mechanism in the emergence of psychosis. Here, we used resting-state functional MRI to examine striatocortical functional connectivity in 22q11.2DS patients. We used a 2 × 2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The associations of TS with schizophrenia, and schizophrenic psychoses has been described in several case reports (2,12,14), and mosaic karyotype 45,X/46,XX was clearly overrepresented. (7,(59)(60).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The associations of TS with schizophrenia, and schizophrenic psychoses has been described in several case reports (2,12,14), and mosaic karyotype 45,X/46,XX was clearly overrepresented. (7,(59)(60).…”
Section: Discussionmentioning
confidence: 78%
“…Although TS is not associated with any psychiatric syndrome, the different features speci c to TS also seem to place individuals at biologically greater risk for depression than individuals unaffected by TS (1,(9)(10)(11). In addition, several case reports have described associations of TS with schizophrenia, and schizophrenic psychoses (2,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…13 Haploinsufficiency of the COMT gene gives rise to an increased dopamine level, which inhibits prefrontal cognitive functioning and may lead to a high rate of psychosis and other psychiatric disorders. 14 A meta-analysis of health-related quality of life in patients with PID found that children and young adults with PID have a lower quality of life than healthy controls. Patients and their parents were assigned the lowest scores for emotional measurements.…”
Section: Controlmentioning
confidence: 99%